Complete Circular Genome Sequence of a Multidrug-Resistant Escherichia coli Strain from Cuba Obtained with Nanopore and Illumina Hybrid Assembly - Hernández-Fillor, Rosa Elena; Brilhante, Michael; Espinosa, Ivette; Perreten, Vincent (Microbiology resource announcements, 2019)
The complete genome sequence of a multidrug-resistant Escherichia coli strain isolated from a healthy pig in Cuba was determined using short and long reads. This strain carried four plasmids, including a 42,683-kb IncX1 plasmid, which contains the third-generation cephalosporin resistance gene bla CTX-M-32 together with other disinfectant and antibiotic resistance genes. The complete genome sequence of a multidrug-resistant Escherichia coli strain isolated from a healthy pig in Cuba was determined using short and long reads. This strain carried four plasmids, including a 42,683-kb IncX1 plasmid, which contains the third-generation cephalosporin resistance gene bla CTX-M-32 together with other disinfectant and antibiotic resistance genes.